The potential of cellulose nanocrystals in tissue engineering strategies - Domingues, Rui M. A. (2014)
Cellulose nanocrystals (CNCs) are a renewable nanosized raw material that is drawing a tremendous level of attention from the materials community. These rod-shaped nanocrystals that can be produced from a variety of highly available and renewable cellulose-rich sources are endowed with exceptional physicochemical properties which have promoted their intensive exploration as building blocks for the design of a broad range of new materials in the past few decades. However, only recently have these nanosized substrates been considered for bioapplications following the knowledge on their low toxicity and ecotoxicological risk. This Review provides an overview on the recent developments on CNC-based functional biomaterials with potential for tissue engineering (TE) applications, focusing on nanocomposites obtained through different processing technologies usually employed in the fabrication of TE scaffolds into various formats, namely, dense films and membranes, hierarchical three-dimensional (3D) porous constructs (micro/nanofibers mats, foams and sponges), and hydrogels. Finally, while highlighting the major achievements and potential of the reviewed work on cellulose nanocrystals, alternative applications for some of the developed materials are provided, and topics for future research to extend the use of CNCs-based materials in the scope of the TE field are identified.